An Experimental Study of the Drag of Various Shape Axisymmetric Bodies Using the Mini C-2 Subsonic Wind Tunnel - L. PABILONA , LEONEL; L. SANTOS Ph.D, ELISEO (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
The C-2 subsonic wind tunnel in MSU-IT College of Engineering is a relatively small wind tunnel resulting to constricted flow of air for large specimen. This constriction resulted to deviation from an open-air environment supposed to be simulated by the wind tunnel. The study focused on this deviation. The drag forces using different sizes and shapes of axisymmetric body at different free stream velocities were measured. A correction for the supporting spindle was incorporated in the determination of the drag force. The correction was based on the whole and shortened spindle. The drag force of models was converted into a drag coefficient obtained by dimensional analysis and then compared to the published value found in the available textbooks and online documents. The results confirm that the drag coefficients of all models with sizes no 50-mm and 75-mm in characteristic lengths consistently fall within the vicinity of the published value with correction based on the whole g shortened spindles. The drag coeffcuents with sizes near to15-mm and 25. mm in characteristic lengths are close to the said value only if the correction is based on the shortened spindle. For sizes near 100 mm in characteristic lengths of sharp edged bodies, the results are consistently higher than the published values illustrating the effect of the constriction.